2023
DOI: 10.3390/polym15081830
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Sandblasted PEEK with Dental Methyl Methacrylate-Based Cement or Composite-Based Resin Cement

Abstract: Poly-ether-ether-ketone (PEEK) is commonly employed in dental prostheses owing to its excellent mechanical properties; however, it is limited by its low bond strength with dental resin cement. This study aimed to clarify the type of resin cement most suitable for bonding to PEEK: methyl methacrylate (MMA)-based resin cement or composite-based resin cement. For this purpose, two MMA-based resin cements (Super-Bond EX and MULTIBOND II) and five composite-based resin cements (Block HC Cem, RelyX Universal Resin C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Küçükekenci et al [13] revealed in their study, the importance of surface pretreatment of PEAK and its significance on the shear bond strength with resin composite veneers. Hata et al [36] concluded that the combination of MMA containing adhesive primer (Visiolink and Signum bond), and resin cement after air abrasion with alumina particles could significantly improve the bond strength. Turkkal et al [37] concluded that surface pretreatment had a significant role in the adhesive failure of bi-layered restorations regardless of the veneering material strength.…”
Section: Discussionmentioning
confidence: 99%
“…Küçükekenci et al [13] revealed in their study, the importance of surface pretreatment of PEAK and its significance on the shear bond strength with resin composite veneers. Hata et al [36] concluded that the combination of MMA containing adhesive primer (Visiolink and Signum bond), and resin cement after air abrasion with alumina particles could significantly improve the bond strength. Turkkal et al [37] concluded that surface pretreatment had a significant role in the adhesive failure of bi-layered restorations regardless of the veneering material strength.…”
Section: Discussionmentioning
confidence: 99%